Guaranteeing digital and information rights in Ukraine: constitutional aspects of introducing the institute of the ombudsman - Karnaukh, Olena; Letnyanchin, Lybomir (Problems of legality, 2026)
The relevance of this study is determined by the need to improve mechanisms for the protection of digital and informational rights in Ukraine, driven by global societal digitalization and the intensification of armed aggression by the russian federation. The aim of the research is to conduct a systematic analysis of the issues surrounding the safeguarding of digital and informational rights, to substantiate the necessity of establishing the institution of the Ombudsman of the Verkhovna Rada of Ukraine for Digital and Informational Human Rights, and to develop conceptual proposals regarding its functioning. The research employs comparative-legal methods (examining national and international legislation), historical-legal analysis, formal-logical reasoning, and methods of analysis and synthesis. The study identifies gaps in the current system for protecting digital and informational rights, particularly the lack of adequate parliamentary oversight and the insufficiency of mechanisms for responding to violations, and proposes a conceptual framework for the ombudsman institution. Prospects for further research include developing mechanisms for interaction between the commissioner and other state institutions, as well as determining effective tools to evaluate the efficiency of activities in the field of digital and informational rights protection.